Social media crisis communications : preparing for, preventing, and surviving a public relations #fail - Hurk, Ann Marie Van den (Que, 2013)
Plan, Prepare, React, and Get Ahead Of Any Crisis- In Real Time! Your business or organization will face a crisis. That's a fact . Here's another : Thanks to social media, crises happen more often and accelerate out of control faster- much faster . So...what's your crisis communications plan? Don't have one? Let's fix that. Now . This book gives you a crisis communications blueprint that's fast, flexible, realistic, complete, and doable . You'll learn how to successfully defend yourself using the same social tools others are using against you. You'll see what works (and doesn't ). You'll learn from folks who've been there and lived to talk about it: leaders who've been forced to execute their own crisis plans in the most brutally tough situations. When that crisis comes, you'll own this book. You'll be ready. You'll survive. You will win . Understand the radically new dynamics of today's crises Anticipate what might happen, so you can get ahead of any crisis Establish crisis response roles, teams, and notification/activation processes Use free and low-cost services to monitor online chatter for signs of trouble Respond in real time, before your crisis escalates Calibrate your response to the realities of what's happening Effectively integrate social media best practices throughout your response Avoid the disastrous mistakes panicked organizations often make Regain control of your organization's identity across the web.